2020
DOI: 10.1111/and.13562
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma protein networks and enriched functions in varicocele: Effect of smoking

Abstract: To verify a possible synergistic effect of smoking and varicocele on the seminal plasma proteome and biological functions, a cross‐sectional study was performed in 25 smokers and 24 nonsmokers. Samples were used for conventional semen analysis, functional analysis (DNA fragmentation, acrosome integrity and mitochondrial activity) and proteomics by a shotgun approach. Functional enrichment of biological pathways was performed in differentially expressed proteins. Smokers presented lower ejaculate volume (p = .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Fifty-two papers were excluded because of the study design, the patients enrolled, or the study outcome. Seventeen articles were finally included [22,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. These articles were then classified into those investigating SP proteome in patients with an increased OS [22,26,27,34,37,41] and thoseinvestigating SP proteome in patientswith diseasestypicallyassociated with increased OS (e.g., varicocele, male accessoryglandinfection/inflammation (MAGI), smoke, obesity) [28][29][30][31][32][33]35,36,[38][39][40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-two papers were excluded because of the study design, the patients enrolled, or the study outcome. Seventeen articles were finally included [22,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. These articles were then classified into those investigating SP proteome in patients with an increased OS [22,26,27,34,37,41] and thoseinvestigating SP proteome in patientswith diseasestypicallyassociated with increased OS (e.g., varicocele, male accessoryglandinfection/inflammation (MAGI), smoke, obesity) [28][29][30][31][32][33]35,36,[38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the substances contained in cigarette smoke, such as cadmium and nicotine, are capable of generating free radicals. The role of OS in smokers is confirmed by the overexpression of the S100A9 protein that, as mentioned above, has been found overexpressed in patients with an increased ROS production [28]. S100A9 belongs to the group of calcium-binding proteins that have the EF-hand domain and binds to pro-inflammatory receptors to start the inflammatory cascade) [59].…”
Section: Cigarette Smoking Oxidative Stress and Seminal Plasma Proteomementioning
confidence: 85%
See 1 more Smart Citation
“…As the purpose of this review was to constitute a list of sperm proteins deregulated by each risk factor, we considered only studies focusing on the risk factor itself, trying to avoid the synergic effects caused by other clinical disorders. For instance, we did not include in this review studies on smoking men with varicocele (e.g., [ 29 , 30 ]). Moreover, only studies focusing on changes at the protein level were considered for this review, thereby excluding RNA and post-translational modification analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Further, it seems that smoking has a synergistic effect with varicocele on SP proteome, and a cross-sectional study revealed that varicocele smokers presented lower mitochondrial activity and acrosome integrity and higher DNA fragmentation compared with non-smokers. Ninety-one proteins, including neprilysin, beta-defensin 106A, and histone H4A, were dysregulated, which indicated that smoking triggers the establishment of inflammatory protein pathways in the testis/epididymis with varicocele [ 47 ]. Additionally, for men with normal fertility, smoking has an adverse impact on functional aspects of sperms such as sperm DNA damage and the destruction of acrosomes’ integrity.…”
Section: Protein Compositions Of Spmentioning
confidence: 99%